Gamified eXtended Reality Potential for Kenyah and Kayan Traditional Medicine Knowledge Transfer and Preservation - Ally Dian, Hendrick; Suriati Khartini, Jali; Nurul Farizah, Ridzuan; Jane, Labadin; Abby Lian, Hendrick; Juna, Liau (2025)
The rapid modernization of Sarawak presents a significant threat to the preservation of traditional knowledge within its indigenous communities. Among the most vulnerable aspects is traditional medicinal knowledge, an intangible cultural heritage at risk of fading without immediate intervention. To address this challenge, this study investigates the potential of an extended reality-based application designed to facilitate the dissemination of traditional medicinal knowledge. The application integrates gamified augmented reality and non-immersive virtual reality elements. Its effectiveness is evaluated using the System Usability Scale, Intrinsic Motivation Inventory, Augmented Reality Sickness Questionnaire, observational analysis, and open-ended qualitative feedback. The findings provide insights into the usability of the application, its capacity to enhance user engagement, and critical design considerations for developing extended reality-based tools aimed at preserving and transmitting traditional medicinal knowledge.